2018
DOI: 10.1101/300343
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Precise tracking of vaccine-responding T-cell clones reveals convergent and personalized response in identical twins

Abstract: These authors contributed equally.T-cell receptor (TCR) repertoire data contain information about infections that could be used in disease diagnostics and vaccine development, but extracting that information remains a major challenge. Here we developed a statistical framework to detect TCR clone proliferation and contraction from longitudinal repertoire data. We applied this framework to data from three pairs of identical twins immunized with the yellow fever vaccine. We identified 500-1500 responding TCRs in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Specifically, the recruitment of novel vaccine-specific T-cell clonotypes into memory compartment following vaccination can be tracked by examining the CD4 memory TCRβ repertoire over time. While we observed no increase in the frequency of the vaccine-specific memory T-cells, as the time point may have missed the peak of the clonal expansion of effector CD4 T cells as was reported before (Blom et al, 2013; Kohler et al, 2012; Pogorelyy et al, 2018), a significant rise in the number of unique vaccine-specific T-cell clonotypes was detected. This observation is consistent with earlier studies of T cell immune repertoire that showed that antigen-specific TCRβ sequences do not always overlap with those sequences that increase in frequency after infection or vaccination (DeWitt et al, 2015).…”
Section: Discussionsupporting
confidence: 48%
“…Specifically, the recruitment of novel vaccine-specific T-cell clonotypes into memory compartment following vaccination can be tracked by examining the CD4 memory TCRβ repertoire over time. While we observed no increase in the frequency of the vaccine-specific memory T-cells, as the time point may have missed the peak of the clonal expansion of effector CD4 T cells as was reported before (Blom et al, 2013; Kohler et al, 2012; Pogorelyy et al, 2018), a significant rise in the number of unique vaccine-specific T-cell clonotypes was detected. This observation is consistent with earlier studies of T cell immune repertoire that showed that antigen-specific TCRβ sequences do not always overlap with those sequences that increase in frequency after infection or vaccination (DeWitt et al, 2015).…”
Section: Discussionsupporting
confidence: 48%
“…A clonotype expansion of 10 4 (not unexpected in the context of an immune response, see e.g. [ 35 ]) would be sufficient to explain this result.…”
Section: Discussionmentioning
confidence: 76%
“…Probability estimates from these models can be used to draw important biological conclusions. For example, observing sequences that are amplified in a repertoire indicates that they perform important functions like targeting yellow fewer or cytomegalovirus (Pogorelyy et al, 2018c; Pogorelyy et al, 2018d; Emerson et al, 2017). However, in order to properly define amplification, we must infer the frequency of such sequences appearing in the naive (i.e.…”
Section: Introductionmentioning
confidence: 99%